Students’ Critical Thinking Skills in Group Discussion: The Case Study of Fifth Grade Students in Sukma Bangsa Bireuen Elementary School - Asrita, Asrita; Nurhilza, Nurhilza (Sukma: Jurnal Pendidikan, 2018)
This study is concerned with group discussion as one of the teaching methods can identify the emergence of students’ critical thinking skills in fifth grade students of Sukma Bangsa School. The purpose of this study was classified fourteen critical thinking concepts (practice, action, management, appreciation, awareness, care, evaluation, understanding, analysis, appraisal, interpretation, being, reflection, reviewing) which emerged in the learning process using group discussion. The study showed that eleven critical thinking concepts (practice, action, management, appreciation, awareness, care, evaluation, understanding, analysis, appraisal, interpretation) could be found in fifth grade students, while three of them  are missing (being, reflection, reviewing). It could be concluded that the students’ ability to think critically was developed after getting experiences in learning by using group discussion. However, an important factor in fostering students’ critical thinking skills was teachers’ involvement. Thus, teachers need to fully participate to stimulate students to express their critical thinking skills in the learning process.[Artikel ini membahas tentang diskusi group sebagai salah satu metode mengajar dapat mengindentifikasi terbentuknya kemampuan siswa dalam berpikir kritis terutama siswa kelas 5 di Sekolah Sukma Bangsa. Tujuan dari penelitian ini adalah mengklasifikasi 14 konsep berpikir kritis (praktik, aksi, manajemen, appresiasi, awareness, peduli, evaluasi, pemahaman, analisa, appraisal, interpretasi, being, refleksi, dan mereview) dapat muncul dalam proses pembelajaran dengan menggunakan diskusi group. Hasil penelitian menunjukkan bahwa tujuh konsep berpikir kritis (praktik, aksi, managemen, appresiasi, awareness, peduli, evaluasi, pemahaman, analisis, appraisal dan interpretasi) telah ditemukan pada siswa kelas 5, sementara tiga lainnya tidak (being, refleksi dan review). Sehingga dapat disimpulkan bahwa kemampuan siswa untuk berpikir kritis telah terbentuk setelah melalui proses pembelajaran dengan menggunakan diskusi group. Meskipun fakor terpenting untuk memunculkan kemampuan siswa berpikir kritis adalah keterlibatan seorang guru. Maka guru-guru perlu berperan aktif menstimulasi siswa untuk mengeluarkan kemampuan berpikir kritisnya dalam proses pembelajaran.]